2013
DOI: 10.4103/0974-9233.114790
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of tearing in patients seen in an oculoplastic clinic in Saudi Arabia

Abstract: Aim:To determine the prevalence of various causes of tearing among patients referred to an oculoplastic clinic.Materials and Methods:A prospective study on all patients seen in an oculoplastic clinic with a chief complaint of tearing. The cause of tearing was determined on the basis of the anatomical location of the primary etiology.Results:This study included 357 patients with a mean age 53.9 years. Punctal stenosis was the most common etiology, affecting 37.8% of the patients. Among patients with punctual st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 6 publications
3
19
1
Order By: Relevance
“…Similarly, in another study, it was reported that 54.6% of the patients had complaints for ≤6 months, and 15.7% of them had it for ≥1 year. It was also observed that the group with the complaint of nasolacrimal duct obstruction had it for a longer period [7]. In our study, 49.7% (81/163) of the patients reported that they had complaints from 1 month to 1 year, 41.1% (67/163) of them had complaints between 1 and 5 years, and 4.3% (7/163) of them had complaints for ≥5 years.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Similarly, in another study, it was reported that 54.6% of the patients had complaints for ≤6 months, and 15.7% of them had it for ≥1 year. It was also observed that the group with the complaint of nasolacrimal duct obstruction had it for a longer period [7]. In our study, 49.7% (81/163) of the patients reported that they had complaints from 1 month to 1 year, 41.1% (67/163) of them had complaints between 1 and 5 years, and 4.3% (7/163) of them had complaints for ≥5 years.…”
Section: Discussionsupporting
confidence: 63%
“…Dry eye and/or chronic blepharitis may affect the corneal and conjunctival neurosensorial receptors and cause reflex hypersecretion of the lacrimal gland [18]. Although rates of 22–29.2% were found in some studies of oculoplastic clinics, increased rate of 40% was also observed in other studies [2, 57]. The researchers concluded that, with these high rates, the assumption that epiphora was synonymous of lacrimal system obstruction was dispelled [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However their study covered seven years period and involved all minor procedures like incision and curettage which were excluded in this study 1 . Many other studies reported the incidence of various individual procedures 2,[5][6][7] . The low incidence could be because of the young age of the oculoplastic subspecialty with limited available facilities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to social embarrassment, tearing can affect the quality of a patient's life as it may interfere with daily activities, especially reading and driving. [1] Although various pathologies can present as tearing most of the ophthalmologists take the nasolacrimal abnormalities into the consideration firstly. There is a controversy between dryness and tearing, but it is wellknown that there may be an annoying reflex tearing in dry eye patients.…”
Section: Introductionmentioning
confidence: 99%